2018
DOI: 10.1164/rccm.201801-0105oc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Antioxidant-enriched Multivitamin in Cystic Fibrosis. A Randomized, Controlled, Multicenter Clinical Trial

Abstract: Antioxidant supplementation was safe and well tolerated, resulting in increased systemic antioxidant concentrations and modest reductions in systemic inflammation after 4 weeks. Antioxidant treatment was also associated with a lower risk of first pulmonary exacerbation. Clinical trial registered with www.clinicaltrials.gov (NCT01859390).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 44 publications
1
23
0
1
Order By: Relevance
“…The first study, with a novel antiinflammatory approach in which the investigators used a multivitamin with additional antioxidants, hypothesized that increased systemic antioxidant concentrations would result in an antiinflammatory effect (NCT01859390). Although elevated antioxidant concentrations were achieved, only modest reductions in systemic inflammation after 4 weeks were observed (circulating calprotectin mean difference, 20.13 log 10 [mg/ml]; P = 0.03) (19) A second study assessed the impact on LCI of preventive hypertonic saline in infants with CF who were less than 4 months of age (NCT01619657) (20). The authors found that early introduction of 6% hypertonic saline significantly improved LCI and weight.…”
Section: Clinical Trials Evaluating Early Interventions To Delay Progmentioning
confidence: 99%
“…The first study, with a novel antiinflammatory approach in which the investigators used a multivitamin with additional antioxidants, hypothesized that increased systemic antioxidant concentrations would result in an antiinflammatory effect (NCT01859390). Although elevated antioxidant concentrations were achieved, only modest reductions in systemic inflammation after 4 weeks were observed (circulating calprotectin mean difference, 20.13 log 10 [mg/ml]; P = 0.03) (19) A second study assessed the impact on LCI of preventive hypertonic saline in infants with CF who were less than 4 months of age (NCT01619657) (20). The authors found that early introduction of 6% hypertonic saline significantly improved LCI and weight.…”
Section: Clinical Trials Evaluating Early Interventions To Delay Progmentioning
confidence: 99%
“…Fat soluble vitamin deficiency is common in CF, and “CF‐specific” multivitamins including water soluble forms of vitamins A, D, E, and K are commonly prescribed to reduce the risk of deficiencies and their complications. A new formulation of an oral antioxidant‐enriched multivitamin supplement was studied to evaluate effects on antioxidant concentrations, markers of inflammation and oxidative stress, and clinical outcomes in an investigator‐initiated, multicenter, randomized, double‐blind, controlled trial . Seventy‐three pancreatic‐insufficient subjects 10 years of age and older with FEV1pp 40% to 100% were randomized to 16 weeks of the antioxidant‐enriched multivitamin or a control multivitamin without antioxidant enrichment.…”
Section: Multisystem Effects Of Cystic Fibrosismentioning
confidence: 99%
“…IQR] 1301 kcal/d vs 686; P < .0001) and proportion of energy intake (median [IQR] 44%[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] vs 31%[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]; P < .0001). Thus, while children with CF met their energy requirements and ate ample fat, this was largely due to ingestion of EDNP foods.…”
mentioning
confidence: 99%
“…There continues to be a great deal of effort directed towards new drug development that targets symptomatic aspects of CF, with numerous drugs in the therapeutic pipeline . These include strategies to normalize epithelial sodium transport (eg, inhibitors of the epithelial sodium channel), agents which reduce or help to resolve inflammation, muco‐active compounds, novel anti‐infective therapies, and treatments that address nutritional and GI aspects of CF disease . In addition to these more traditional targets, clinical trials testing highly novel strategies are underway, such as allogenic human mesenchymal stem cells (NCT02866721), iron chelators to disrupt microbial biofilms (NCT02354859), and inhaled nitric oxide that target difficult to treat CF infections (NCT02498535, NCT01958944).…”
Section: Established Symptom‐based Therapy For Cfmentioning
confidence: 99%
“…sodium transport (eg, inhibitors of the epithelial sodium channel), agents which reduce or help to resolve inflammation, muco-active compounds, novel anti-infective therapies, and treatments that address nutritional and GI aspects of CF disease. [12][13][14][15][16][17][18][19] In addition to these more traditional targets, clinical trials testing highly novel strategies are underway, such as allogenic human mesenchymal stem cells (NCT02866721), iron chelators to disrupt microbial biofilms (NCT02354859), and inhaled nitric oxide that target difficult to treat CF infections (NCT02498535, NCT01958944). These approaches focus on important disease pathologies downstream of the genetic defect causing CF and can be applied to CF patients independent of their background genotype.…”
mentioning
confidence: 99%